Sex-Based Differences in the Myogenic Response and Inflammatory Gene Expression Following Eccentric Contractions in Humans - Fortino, Stephen A.; Wageh, Mai; Pontello, Riley; McGlory, Chris; Kumbhare, Dinesh; Phillips, Stuart M.; Parise, Gianni (Frontiers in Physiology, 2022)
After muscle injury, the interaction between muscle satellite cells (SC) and the immune response is instrumental for the repair and regeneration of skeletal muscle tissue. Studies have reported sex-based differences in the skeletal muscle inflammatory and regenerative response following injury. However, many of these studies investigated such differences by manipulating the concentration of estradiol, in rodents and humans, without directly comparing males to females. We sought to explore differences in the myogenic and inflammatory response following unaccustomed eccentric exercise in males and females. We hypothesized that females would have a blunted myogenic and inflammatory response as compared to males. Methods: 26 (13 male, 13 female) healthy young adults (22 ± 0.4 years [mean ± SEM]) performed 300 maximal eccentric contractions (180°/s) of the knee extensors. Muscle biopsies were taken before (pre) and 48 h (post) following eccentric damage. SC content and activation were determined by immunohistochemical and real time-polymerase chain reaction (rt-PCR) analysis. Inflammatory markers were analyzed using rt-PCR. Results: Following eccentric damage, males had a greater expansion of type I-associated SC (p < 0.05), and there was a trend for a greater expansion in total SC (type I + II fibers) (p = 0.06) compared to females. There was a trend for a greater increase in Pax7 and CCL2 gene expression in males compared to females (p = 0.09). Conclusion: We conclude that there are sex-based differences in the myogenic and inflammatory response, where females have a blunted SC and inflammatory response.